Assessment of periglacial response to increased runoff: An Arctic hydrosystem bears witness. (11th September 2018) - Bernard, Eric; Friedt, Jean Michel; Schiavone, Sophie; Tolle, Florian; Griselin, Madeleine
Abstract: In the general context of global warming, the cryosphere appears as an environment that exhibits a strong sensitivity to climate variations. Overall, glacier systems are now known to be reliable indicators of climate trends. Although glacier dynamics are subject to international monitoring networks, periglacial environments are much less observed. However, these newly deglaciated areas get wider since glaciers are retreating, and their dynamics become increasingly significant. The observed increase in water fluxes, temperature and precipitation, permafrost melting, and reduced cold periods induce a combined control on modifications of the glacier and periglacial dynamics. Such consequences are also visible on the landscape, hinting at an adaptation of the environment to the climatic forcing. The work carried out focuses on Austre Lovénbreen area, a small 10‐km 2 glacier basin (Svalbard, 78.87°N, 12.15°E, west coast of Spitsbergen) exhibiting typical arctic glacial retreat trends. Its geomorphological characteristics as well as its observatory status make it an appropriate control area. Our investigations are based on a combination of classical on‐site snow, ice, and geomorphological measurements, combined with innovative methods using aerial photography (e.g., from unmanned aerial systems) and digital photogrammetric image processing. Such data currently complement classical remote sensing methods (satellite imagery), providing both improved resolution and high temporal repeatability. Indeed, short acquisition time and flexibility allows measurements within very short time intervals, a requirement when short events are significant in the whole system evolution: The speed at which climatic change‐related events occur requires such fine‐grained spatial and temporal monitoring. This work highlights an increase of sediment transfers during the last decade that ties in with the increasing liquid precipitation as well as a trend of rising temperatures. The newly deglaciated area, particularly at the glacier front, is in constant and fast reshaping, which is quantifiable from 1 year to another, assessing the increase of periglacial landscape modification. This small‐scale detailed analysis enlightens on global processes occurring in Arctic regions demonstrating ongoing geomorphological and landscape changes as a consequence of glacier retreat and newly exposed periglacial environments.